Spring burning of native tallgrass pastures influences diet composition of lactating and non-lactating beef cows - N.A. Aubel; G.J. Eckerle; L.A. Pacheco; M.J. Macek; L.R. Mundell; K. C. Olson; John R. Jaeger; Leigh W. Murray (Kansas Agricultural Experiment Station Research Reports, 2012)
Diet selection is a dynamic process because of seasonal changes in animal and plant characteristics. Nutrient requirements of grazing animals are a function of physiological state; moreover, plant characteristics may be altered with prescribed spring burning of native rangelands. Prescribed spring burning is used to improve the average quality of pasture forage by removing old growth and making new plant growth more accessible to grazing cattle. Microhistological analysis of fecal material has been a widely used method for quantifying the botanical composition of a grazing animal's diet since it was first described by Baumgartner and Martin in 1939. Little research has been conducted on how diet selection preferences of lactating beef cows with suckling calves and non-lactating beef cows are influenced by prescribed burning. We hypothesized that during the summer grazing season, lactating cows with calves and non-lactating cows would display distinctive preferences for certain species. Furthermore, we anticipated that these diet selection preferences might be influenced by prescribed burning. To that end, our objective was to characterize differences in diet selection between lactating beef cows suckling calves and non-pregnant, non-lactating beef cows grazing either burned or unburned native tallgrass prairie during summer.
Keywords: Cattlemen& #x27; s Day; 2012; Kansas Agricultural Experiment Station contribution; no. 12-231-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1065; Beef Cattle Research; 2012 is known as Cattlemen& #x27; s Day; Beef; Native tallgrass pastures; Lactating beef cows; Non-lactating beef cows